Sustainable Design HCI, Usability and Environmental Concerns - Issa, Tomayess; Isaias, Pedro (Springer London : Imprint: Springer, 2015)
This book is concerned with the importance of Human Computer Interaction (HCI), Usability, user participants, and Sustainability in the Information Communication Technology (ICT) industry throughout the world. ICT has become a crucial instrument for communication, entertainment, commerce and research and this increased usage is presenting new environmental and sustainability issues as we try and meet the ever growing needs of both businesses and individuals. Sustainability must become central to the design of new technologies to make a concerted effort to tackle the environmental concerns we face now and for the future. Development frameworks, tools and models are used and explored and the New Participative Methodology for Sustainable Design (NPMSD) is introduced as a way of identifying key factors needed in developing more sustainable systems including new smart technology and portable devices. Additional research will be carried out in the future to assess the sustainable design step using larger, more diverse countries with developed and developing economies to ensure compliance with environmental standards and rules for sustainable systems. Sustainable Design will  be an invaluable resource for students and researchers, designers and business managers who are interested in the human-centred, environmental concerns of sustainable technologies. .